Ensuring competitiveness of the auto dealer companies - E. Kuptsova (Publishing House of the State University of Management, 2016)
Basic factors of competitiveness of the auto dealer companies are considered and analysed. In article noted that the competitiveness assessment from positions of consumers and owners is necessary. The algorithm of actions for development of the system of management of competitiveness of the auto dealer company is offered.